2019
DOI: 10.16986/huje.2019052870
|View full text |Cite
|
Sign up to set email alerts
|

The Gamification Tool For The Classroom Response Systems: Kahoot

Abstract: Öğretim süreci boyunca öğrencilerden anında geri bildirim toplamak için kullanılan sınıf cevap sistemleri (SCS), geçmişte ve günümüzde farklı isimlerle altında kullanılmıştır. Bu isimlere örnek olarak soru-cevap sistemleri, öğrenci yanıt sistemleri, elektronik yanıt sistemleri veya bulut tabanlı sınıf yanıt sistemleri verilebilir. Bu çalışmanın amacı, dönüştürülmüş öğrenmeyi süreçlerinde kullanan eğitimcileri, öğrencilerin Kahoot kullanımı hakkındaki algıları hakkında bilgilendirmektir. Karma yöntem ile gerçek… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 6 publications
0
5
0
2
Order By: Relevance
“…While the traditional student response system is a useful method for measuring the cognitive status of students for the teacher, gamified response systems are more exciting and motivating for students during the exam (Wang, 2015). Gündüz and Akkoyunlu (2020) suggested that teachers' using classroom response systems while planning class activities can increase motivation for the course. Bury (2017) researched online assessment tools and concluded that they provide immediate feedback and improve students' grammar knowledge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the traditional student response system is a useful method for measuring the cognitive status of students for the teacher, gamified response systems are more exciting and motivating for students during the exam (Wang, 2015). Gündüz and Akkoyunlu (2020) suggested that teachers' using classroom response systems while planning class activities can increase motivation for the course. Bury (2017) researched online assessment tools and concluded that they provide immediate feedback and improve students' grammar knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have revealed that Kahoot! has a positive effect on motivation (Al-Hadithy & Ali, 2018;Gündüz & Akkoyunlu, 2020;El-tahir et al, 2021;Purba et al, 2019). It is thought that Kahoot!…”
mentioning
confidence: 99%
“…They find learning to be more fun and interesting. This is under research conducted by (Yuruk, 2019: Gündüz & Akkoyunlu, 2020Marsa et al, 2021), which states the use of Kahoot! Games make the learning environment more fun.…”
Section: Students' Perception 0n Learning Reading Comprehension On Descriptive Text Using Kahoot! Gamementioning
confidence: 99%
“…One of the most widely used CRS is Kahoot [20,36], an application to assess the extent to which content is already dominated by students. It is a free online tool that allows the implementation of quick questionnaires to assess the knowledge of students in real-time.…”
Section: Introductionmentioning
confidence: 99%